${ω_{\mathcal{I}, γ}}$}-continuous functions and weakly {\boldmath${ω_{\mathcal{I}, γ}}$}-continuous functions - Carpintero, C.; Rosas, E.; Salas-Brown, M.; Vásquez, L. (Sarajevo Journal of Mathematics, 2024)
Using the $ω_{\mathcal{I}, γ}$-closed sets defined in \cite{carpintero}, we introduce the notions of $ω_{\mathcal{I}, γ}$-continuous functions and weakly $ω_{\mathcal{I}, γ}$-continuous functions. Characterizations and properties of this new class of functions are obtained and studied. 2010 Mathematics Subject Classification. 54C10, 54D10.